2017
DOI: 10.1115/1.4036647
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Optimization of a Winglet-Shroud Tip Geometry for a Linear Turbine Cascade

Abstract: This paper presents a continued study on a previously investigated novel winglet-shroud (WS) (or partial shroud) geometry for a linear turbine cascade. Various widths of double-side winglets (DSW) and different locations of a partial shroud are considered. In addition, both a plain tip and a full shroud tip are applied as the datum cases which were examined experimentally and numerically. Total pressure loss and viscous loss coefficients are comparatively employed to execute a quantitative analysis of aerodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The flow fields for analysis in this research are solved using ANSYS CFX v14.0. Referring to the previous studies on the tip leakage flow problems of Zhang [10] and Maral [14], Menter's SST turbulence model [15] has been used to approximate the turbulent viscosity in the present study. The fluid mesh has a first layer grid width of 2 × 10 −6 m and the Y plus value is 0.02~2 on the blade.…”
Section: Numerical Methods 221 Mesh Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow fields for analysis in this research are solved using ANSYS CFX v14.0. Referring to the previous studies on the tip leakage flow problems of Zhang [10] and Maral [14], Menter's SST turbulence model [15] has been used to approximate the turbulent viscosity in the present study. The fluid mesh has a first layer grid width of 2 × 10 −6 m and the Y plus value is 0.02~2 on the blade.…”
Section: Numerical Methods 221 Mesh Discretizationmentioning
confidence: 99%
“…Zhang [10] investigated a new winglet-shroud geometry and derived the conclusions that the winglet-shroud design is able to minimize aerodynamic losses due to the common winglet structure when a linkage exists in the middle streamwise position of the winglet. Zhou [11] also designed a multi-parameter control-based tip geometry modeling method based on the winglet structure and obtained a new tip geometry structure with maximum efficiency using a multi-island genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong and Zhou 13 found that the leakage loss in winglet-squealer tip is reduced significantly as compared with the conventional squealer tip. By using the optimization strategies, Maesschalck et al 14 Zhang et al 15 Caloni et al 16 and Zhou et al 17 presented the optimized geometries of winglet and novel designs of squealer-winglet tip, which have shown promising benefits in aerodynamic performance improvement in the tip region. For the heat transfer and film cooling effect, Papa et al, 18 Silva and Tomita, 19 Zhou et al, 20 and Yan et al 21 reported that the winglet extension is beneficial for the heat transfer reduction as compared with the flat tip and conventional squealer tip.…”
Section: Introductionmentioning
confidence: 99%
“…in real products. Relevant researches are very active in axial turbines [1][2][3][4], but comparably rare in axial compressors. Different tip geometry (e.g., crown tip, winglet etc.)…”
Section: Introductionmentioning
confidence: 99%